Formalization of the technology of arranging tactical group trains - Бутько, Тетяна Василівна; Прохорченко, Андрій Володимирович; Киман, Андрій Миколайович (Eastern-European Journal of Enterprise Technologies, 2015)
The study suggests an improved procedure of correcting train formation plans (TFPs) on the basis of calculations on the agreed network arrangement of tactical group trains. Our aim is to improve the Ukrainian technology fortactical acceleration of long-distance and low-capacity train streams that do not meet the current TFPrequirements. The problem can be solved by means of the suggested formalized technology of correcting TFPs on the basis of arranging tactical group trains. The devised mathematical model allows selecting a reasonable route for arranging groups of wagons into agreed group trains with variable combinations of wagon groups within the network. The mathematical model belongs to integer linear programming tasks and can be solved with the help of the genetic algorithm. The suggested approach allows an effective distribution of work between technical sorting stations of the railroad network and ensures timely delivery of cargoes to the customer at the agreed time.